2012
DOI: 10.1111/j.1601-0825.2011.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced alveolar bone loss in a model of non‐invasive periodontitis in rice rats

Abstract: OBJECTIVE The rice rat (Oryzomys palustris) develops periodontitis-like lesions when fed a diet high in sucrose and casein (H-SC). We aimed to establish whether this model can accurately mimic the development of human periodontitis. MATERIALS AND METHODS For this purpose, 28 day-old rice rats (15/group) were assigned to standard (STD) or H-SC diets and sacrificed after 6, 12, and 18 wks. Jaws were processed for morphometric, histometric, histologic, histomorphometric, and microCT analyses. RESULTS We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 35 publications
4
58
0
2
Order By: Relevance
“…But the presence of small quantity of inflammatory cells was found in the underlying connective tissue and exocytosis of these cells into the junctional and sulcular epithelium in all the groups studied. Researchers report that the standard diet offered to rodents for a period from 6 to 18 weeks favors the accumulation of bacterial plaque around the teeth [31]. As a result, some inflammatory cells are attracted to the underlying connective tissue and migrate to the junctional epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…But the presence of small quantity of inflammatory cells was found in the underlying connective tissue and exocytosis of these cells into the junctional and sulcular epithelium in all the groups studied. Researchers report that the standard diet offered to rodents for a period from 6 to 18 weeks favors the accumulation of bacterial plaque around the teeth [31]. As a result, some inflammatory cells are attracted to the underlying connective tissue and migrate to the junctional epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Though this study (Aguirre et al, 2012a) also disclosed a trend for rice rats consuming a pelleted standard (STD) diet to develop tissue level PD, there are currently no long-term studies of PD in STD diet-fed rice rats because of the perceived requirement to feed a H-SC diet to induce PD in rice rats. The STD diet-fed rice rat may have potential as a pre-clinical model that, without dietary intervention, not only complements existing rat models of mild and moderate PD, but also evolves continuously into SP in a sufficiently-compressed timeframe to enable practical studies that address human SP.…”
Section: Introductionmentioning
confidence: 88%
“…We recently confirmed that rice rats consuming a pelleted H-SC diet develop PD, including worsening of both alveolar crest height (ACH) and horizontal (h) alveolar bone height (ABH) (Aguirre et al, 2012a). Though this study (Aguirre et al, 2012a) also disclosed a trend for rice rats consuming a pelleted standard (STD) diet to develop tissue level PD, there are currently no long-term studies of PD in STD diet-fed rice rats because of the perceived requirement to feed a H-SC diet to induce PD in rice rats.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations